Cytoreductive surgery for giant locally advanced intra-abdominal tumors in Uganda. Issue 5 (24th May 2022) - Okello, Michael; Nuwagaba, Julius; Ddungu, Henry; Okuku, Fred Machyo
Abstract: Cytoreductive surgery is removal of tumor as much as possible when complete resection is impossible because of advanced disease. It is a management option for giant intra-abdominal tumors with pressure symptoms. We present three patients who underwent cytoreductive surgery for giant intra-abdominal tumors between May 2019 and November 2021. Patient 1 had a gastrointestinal stromal tumor (GIST) involving stomach, spleen and transverse colon. En bloc resection of the GIST with the involved viscera was done. Patient 2 had a liposarcoma measuring 25.8 × 19.6 × 15.3 cm infiltrating the stomach, spleen and the left hemidiaphragm. Involved viscera and liposarcoma were resected en bloc. Patient 3 had a liposarcoma measuring 40 × 35 × 12 cm and encasing the left ureter. Mass was excised together with part of the left ureter and left ureter reconstructed. Giant intra-abdominal tumors are rare. Involvement of adjacent structures may necessitate multivisceral resections with or without organ reconstruction.